Management of disaster risk program in the First District of Zamboanga del Norte - Campiseño, Lemuel R.; Oga, Chery May M. (2015)
The study aimed to look into the disaster risk program management in the first district of Zamboanga del Norte and to find out the disaster prevention and mitigation which includes knowledge and awareness of the different disasters and disaster preparedness and response. The study planned to offer recommendations that would help address disaster risk reduction brought about by the different hazards in the first district of Zamboanga del Norte. The study used the qualitative method of research which utilized the results of various studies on knowledge, preparedness and awareness on disaster in the first district of Zamboanga del Norte. It was found out that the community was less knowledgeable while the political leaders were equipped with knowledge for they have attended several trainings and seminars on disaster. Preparedness on disaster has very much to do with knowledgeable and awareness. There was an association between knowledge and awareness to preparedness. Disaster Risk Reduction Management should be properly employed in the community.
Keywords: Emergency management -- Zamboanga del Norte; Mindanao studies